Comparative treatment between anti-parasitic drugs and drugs combined with herlth education in intestinal protozoa in thai school children - Amorn Lekkla (2015)
Joint International Tropical Medicine 2002: the 8th Chamlong-Tranakchit Harinsuta Lecture 20-22 November 2002 Montien Riverside Hotel, Bangkok, Thailand: abstract. Bangkok: Faculty of Tropical Medicine, Mahidol University; 2002. p. 196.